Analisis Adopsi Inovasi Teknologi Informasi Menggunakan Innovation Diffusion Theory (IDT) Pada Aplikasi TaniHub di Wilayah Surabaya - Ibrahim; Pratama Puji Ariyanto; Cready Celgie Gildbransen; Primandika Hakiki; Saktian Purborini (Universitas Mercu Buana Yogyakarta, 2023)
TaniHub is a form of information technology development, especially in agriculture. TaniHub allows farmers to sell their crops directly to consumers without going through distributors first, which is one of the advantages for farmers to get more profits than through distributors. However, in its implementation, of course, it does not only produce benefits. There is one problem that is the impact of the adoption of the TaniHub application, namely, traders in traditional markets will potentially experience a decrease in sales and income because consumers can now order directly from farmers without having to buy through traditional markets. The purpose of this study was to analyze the adoption of information technology for the TaniHub application in the Surabaya area using the Innovation Diffusion Theory measuring instrument. In this study, there were as many as 100 research samples or respondents who were obtained online and used the Partial Least Square (PLS) analysis technique. With the results obtained in this study, it is hoped that it can provide an overview of the adoption of the TaniHub application in the Surabaya area, and can encourage other researchers to examine the adoption of TaniHub from a different perspective.